A longitudinal study of team-fan role identity on self-reported attendance behavior and future intentions - Trail, Galen T.; Anderson, Dean F.; Lee, Don (Journal of Amateur Sport, 2017)
Attendance at college sporting events generates billions of dollars annually for athletic departments at the college level in the United States. Based on Identity Theory and prior research, we developed and tested two models that were successful in predicting actual attendance, attendance intentions (conative loyalty), and support for the team across time. Respondents (N = 165; 60% female, 59% Caucasian) filled out three surveys across the year. In Model A (RMSEA = .066, χ2/df = 50.02/29 = 1.73), prior season attendance, number of games intending to attend, and preseason team-fan role identity (Time 1) explained 63% of self-reported attendance behavior (Time 2). Those variables and postseason role identity (Time 2) explained 48.5% of attendance intentions (Time 3; Model A) and 43% of supporting the team in the future (Time 3; Model B, RMSEA = .060, χ2/df = 46.16/29 = 1.59). Sports marketers need to take into account both the impact of role identity as a fan of the team and attendance intentions, not just prior attendance behavior when predicting future attendance behavior and support for the team